The Representation of Anxiety in Inside Out 2 Can Effect the Languages Produces: A Psycholinguistic Study Based on the Sapir-Whorf Hypothesis - Fahira, Ayuke Nurul (CV. Rayyan Dwi Bharata, 2025)
This paper is figure it out the emotional representation of new character anxiety in the animated film Inside Out 2 using a psycholinguistic analysis based on the Sapir-Whorf Hypothesis. This study seeks to explore interactions of language and emotion in expressing Riley's character in the film as she grows into adulthood. The Sapir-Whorf hypothesis asserts that language influences thought and behaviour to serves as a theoretical framework for studying characters' emotional expressions and language use. The study demonstrates that Riley's language and conduct alter dramatically when an apprehensive character appears, in accordance with the ideas of linguistic relativity and determinism. These findings indicate that Riley's language reflects his internal emotional state, particularly when anxiety dominates her perceptions, actions, and relationships with others. The study indicates that Inside Out 2 provides an excellent medium for exploring the complicated interaction between language and emotion to validating the Sapir-Whorf Hypothesis by demonstrating how language shapes and is shaped by emotional character experiences.